New England and the Energy Crisis - Federal Reserve Bank of Boston; Morris, Frank E. (Massachusetts: Federal Reserve Bank of Boston, 1975)
The conference, New England and the Energy Crisis, was an attempt to clarify the choices posed New England by this critical question "will there be sufficient energy in the future, at an acceptable price, to provide the standard of living New Englanders have come to expect?" and, where possible, to develop policy recommendations.
Proceedings of a conference held at Edgartown, Massachusetts October, 1975.
Includes bibliographic footnotes.
ne 26/04/2018
Loan
Keywords: Energy Policy; United States